DataSheet_1_Understanding the Implications of Hydrographic Processes on the Dynamics of the Carbonate System in a Sub-Antarctic Marine-Terminating Glacier-Fjord (53°S).docx - Jurleys P. Vellojin; Gonzalo S. Saldías; Susan E. Allen; Rodrigo Torres; Maximiliano Vergara-Jara; Marcus Sobarzo; Michael D. DeGrandpre; José Luis Iriarte (2022)
The biogeochemical dynamics of fjords in the southeastern Pacific Ocean are strongly influenced by hydrological and oceanographic processes occurring at a seasonal scale. In this study, we describe the role of hydrographic forcing on the seasonal variability of the carbonate system of the Sub-Antarctic glacial fjord, Seno Ballena, in the Strait of Magellan (53°S). Biogeochemical variables were measured in 2018 during three seasonal hydrographic cruises (fall, winter and spring) and from a high-frequency pCO 2 -pH mooring for 10 months at 10 ± 1 m depth in the fjord. The hydrographic data showed that freshwater input from the glacier influenced the adjacent surface layer of the fjord and forced the development of undersaturated CO 2 (< 400 μatm) and low aragonite saturation state (Ω Ar < 1) water. During spring, the surface water had relatively low pCO 2 (mean = 365, range: 167 - 471 μatm), high pH (mean = 8.1 on the total proton concentration scale, range: 8.0 - 8.3), and high Ω Ar (mean = 1.6, range: 1.3 - 4.0). Concurrent measurements of phytoplankton biomass and nutrient conditions during spring indicated that the periods of lower pCO 2 values corresponded to higher phytoplankton photosynthesis rates, resulting from autochthonous nutrient input and vertical mixing. In contrast, higher values of pCO 2 (range: 365 – 433 μatm) and relatively lower values of pH T (range: 8.0 – 8.1) and Ω Ar (range: 0.9 – 2.0) were recorded in cold surface waters during winter and fall. The naturally low freshwater carbonate ion concentrations diluted the carbonate ion concentrations in seawater and decreased the calcium carbonate saturation of the fjord. In spring, at 10 m depth, higher primary productivity caused a relative increase in Ω Ar and pH T . Assuming global climate change will bring further glacier retreat and ocean acidification, this study represents important advances in our understanding of glacier meltwater processes on CO 2 dynamics in glacier–fjord systems.